Is digital financial inclusion good for bank stability and sustainable economic development? Evidence from emerging Asia - Hasanul Banna; Md Rabiul Alam (Asian Development Bank Institute (ADBI), 2021)
In this current era of the fourth industrial revolution, both the negative and positive effects of financial inclusion raise the question of whether digital finance can be a solution for financial stability through attaining sustainable economic growth or not. Hence, considering the aftermath of the 2007.2009 GFC, which had a catastrophic effect on the overall banking industry, this study aims to examine the effect of digital financial inclusion (DFI) on banking stability through promoting sustainable economic development using an unbalanced panel data of 574 banks from seven emerging Asian countries from 2011 to 2018. The results suggest that DFI brings banking stability and an integrated digital financial system among the emerging Asian banks is not merely a way of ensuring banking stability, rather it ensures inclusive and sustainable economic development that helps achieve financial sustainability, which will ultimately lead to achieving the SDGs by 2030.
Keywords: G21; G28; 330; banking stability; digitization; digital finance; sustainable economic development; emerging Asia